Espaços das Migrações Transnacionais: perfil sociodemográfico de imigrantes da África para o Brasil no século XXI - Baeninger, Rosana (2019)
This paper aims to build a sociodemographic profile of African immigration to Brazil. Part of the theoretical contribution of transnational migrations as an analytical resource that articulates the transformations arising from the international division of labor to the processes that occur within national borders. Methodologically, administrative records of several Brazilian institutions are used: Federal Police, National Committee for Refugees and Annual Report of Social Information.